2006
DOI: 10.1002/anie.200601001
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of [ZnR2(L)] Complexes with Dioxygen: A New Look at an Old Problem

Abstract: OR or OOR? The oxygenation of ZntBu2 in the presence of donor ligands demonstrates the tendency of zinc dialkyls to undergo oxidation of only one ZnC bond under controlled conditions (see scheme). The formation of alkoxide or peroxide species is influenced by the type of donor ligand employed, and these divergent pathways offer a glimpse into the general mechanism of dioxygen activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 40 publications
3
71
2
Order By: Relevance
“…[21] The relative base strength of [NEt 3 ] is approximately three times higher than THF, [22] which in turn is a stronger base than THP or furan. [20] [24] and, significantly, four-coordinate alkylzinc complexes of this type have been shown to be resistant to further oxidation. [24] Fig.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[21] The relative base strength of [NEt 3 ] is approximately three times higher than THF, [22] which in turn is a stronger base than THP or furan. [20] [24] and, significantly, four-coordinate alkylzinc complexes of this type have been shown to be resistant to further oxidation. [24] Fig.…”
Section: Introductionmentioning
confidence: 98%
“…[20] [24] and, significantly, four-coordinate alkylzinc complexes of this type have been shown to be resistant to further oxidation. [24] Fig. 2).…”
Section: Introductionmentioning
confidence: 98%
“…The synthesis and characterization of sterically demanding triphenyltin‐alkylzinc‐alkoxy compounds [Ph 3 SnOZnR] 4 (R=Me ( 1 ), Et ( 2 )) are presented. Furthermore, the steric congestion at the zinc atoms in [R 3 SnOZn t Bu] 4 was increased in compound 3 and 4 .Therefore, triorganotin hydroxides R 3 SnOH (R=Me, Ph) were treated with appropriate alkylzinc Lewis bases ZnR’ 2 (R’=Me, Et, t Bu) 14. Products 1 and 2 were isolated as colorless crystals in good yields (70–82 %; Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that besides preventing pre-reaction with oxygen, the adducts also led to the deposition of vertically aligned ZnO nanowires on the Si(1 1 1) substrates at temperatures of $ 500 1C. It was proposed that pre-reaction is suppressed by the formation in the gas-phase of relatively oxygen-resistant species such as [MeZn(OMe)(L)] x , and this is supported by the recent isolation and structural characterization of the oxygen-resistant dimer [Bu t Zn(OBu t )(THF)] 2 [20]. The precise mechanism of ZnO nanowire growth from the [Me 2 Zn(L)] adducts has not been established, but it is proposed that alkylzinc alkoxide intermediates such as [MeZn(OMe)(L)] (L¼cyclic ether) and/or [MeZn(OMe)] play a key role in the gas-phase and surface kinetics of ZnO nanowire formation [19].…”
Section: Introductionmentioning
confidence: 97%